THE PECULIARITIES OF TEXT CATEGORIES AND LITERARY TEXT IN LINGUISTICS - Saidaxmedova Shoxista (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article investigates the problem of text categories and the question of their taxonomy. One of the basis notions in text linguistics is the notion of text categories.